Fenomena Kemerosotan Penggunaan Kalimat Efektif dalam Teks Deskripsi Siswa SMP di Tengah Dominasi Bahasa Media Sosial - Deby Permatasari; Asri Bariqoh; Jatim Desiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2026)
This study aims to describe the types of errors regarding the use of effective sentences in descriptive essays written by seventh-grade students at SMP Ibnu Abu Rasyad Paseyan Sampang, as well as potential remedial measures. The research focuses on identifying errors across several aspects: coherence, conciseness, structural balance, logical consistency, precision, parallelism, and sentence emphasis. A descriptive qualitative method was employed, utilizing data collection techniques such as observation, documentation, and written tests. Data—consisting of 15 student descriptive essays—were analyzed through the stages of data collection, reduction, presentation, and conclusion drawing. The results indicate that the use of effective sentences in the students' essays was not yet optimal. Across the 15 essays, numerous errors were identified: 15 regarding coherence, 12 regarding conciseness, 8 regarding structural balance, 3 regarding logical consistency, 4 regarding precision, 2 regarding parallelism, and 1 regarding emphasis. These findings demonstrate that the majority of students have not yet mastered the ability to construct clear, precise, and communicative sentences in accordance with the principles of effective sentence structure. The study highlights the need for further guidance in writing descriptive essays so that students can produce effective, easily understandable sentences, thereby enhancing their writing proficiency.